The diet of the South American Tern: The Argentine Anchovy as key prey in the non-breeding season - Mariano y Jelicich, Rocío (2011)
The Argentine Anchovy (Engraulis anchoita) is one of the most important pelagic fishery resources of the Patagonian Shelf and is known to be an important prey item for several seabirds of the northern Argentine coast. The South American Tern (Sterna hirundinacea) is endemic to the Atlantic and Pacific coasts of South America and, on the Atlantic coast, breeds from central Brazil to southern Argentina. Large non-breeding flocks form during the austral winter and spring from southern Brazil to northern Patagonia. The diet of the South American Tern was studied over three consecutive nonbreeding seasons through the analysis of regurgitated pellets. The Argentine Anchovy comprised >80% (index of relative importance) of fish prey in the diet, and remained important throughout the study period. Other important fish prey were Cornalito Silverside (Odonthestes incisa), Pejerrey Silverside (O. argentinensis) and Stripped Weakfish (Cynoscion guatucupa). The growing interest in commercially fishing Argentine Anchovies makes it important that studies are conducted to determine the potential effect of the harvest of Anchovies on South American Terns and other top predators.